2010
DOI: 10.1111/j.1600-051x.2010.01632.x
|View full text |Cite
|
Sign up to set email alerts
|

Amoxicillin and metronidazole as an adjunctive treatment in generalized aggressive periodontitis at initial therapy or re-treatment: a randomized controlled clinical trial

Abstract: At 8 months, patients who had antibiotics at initial therapy showed statistically significant benefits compared with those who had antibiotics at re-treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
127
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(138 citation statements)
references
References 23 publications
6
127
0
5
Order By: Relevance
“…A systematic review in 2008 trying to assess the relative benefit of prescribing antibiotics either during the non-surgical or the surgical phase of therapy remained inconclusive [60]. However, two studies, not included in this review, showed better clinical outcomes for subjects with generalized aggressive periodontitis if patients were given amoxicillin and metronidazole immediately after initial scaling and root planing rather than after re-treatment of persisting pathology [61,62]. In 51 patients diagnosed with chronic periodontitis, systemic metronidazole and amoxicillin significantly improved the 6-month clinical outcomes of extensive fullmouth non-surgical periodontal debridement provided in 48 h, thereby significantly reducing the need for additional therapy [49,63].…”
Section: Which Is the Optimal Time Point For Administering Antibiotics?mentioning
confidence: 97%
“…A systematic review in 2008 trying to assess the relative benefit of prescribing antibiotics either during the non-surgical or the surgical phase of therapy remained inconclusive [60]. However, two studies, not included in this review, showed better clinical outcomes for subjects with generalized aggressive periodontitis if patients were given amoxicillin and metronidazole immediately after initial scaling and root planing rather than after re-treatment of persisting pathology [61,62]. In 51 patients diagnosed with chronic periodontitis, systemic metronidazole and amoxicillin significantly improved the 6-month clinical outcomes of extensive fullmouth non-surgical periodontal debridement provided in 48 h, thereby significantly reducing the need for additional therapy [49,63].…”
Section: Which Is the Optimal Time Point For Administering Antibiotics?mentioning
confidence: 97%
“…[7] The combined use of amoxicillin (AMX) and metronidazole (MTZ) has been proposed to exhibit increased bactericidal, and spectral efficacy compared with monotherapy with either drug. [8,9] The combination of MTZ and AMX in the treatment of aggressive periodontitis has gained recognition mostly due to its effectiveness against Aggregatibacter actinomycetemcomitans, a periodontal pathogen closely associated with the etiology of this infection. [10,11] In addition to A. actinomycetemcomitans, this combination is active against Treponema denticola, Tannerella forsythia, Porphyromonas gingivalis, Fusobacterium nucleatum, and Prevotella intermedia.…”
Section: Introductionmentioning
confidence: 99%
“…The preferred combination antibiotic therapy at present for treatment of generalized aggressive periodontitis is 250 mg of amoxicillin thrice daily alone with metronidazole 250 mg twice daily for 8 days 58,62 . It is one of the most evaluated drug combinations in generalized aggressive periodontitis that significantly improves the result and should be preferred over the antibiotic regimens as the first line treatment [63][64][65][66][67][68] . Antibiotics that are bacteriostatic (e.g.…”
Section: Serial and Combination Therapymentioning
confidence: 99%